PENGGUNAAN TEKNIK SNOWBALL THROWING DALAM PENGAJARAN KETERAMPILAN MEMBACA BAHASA INGGRIS - A. Dian Islamiati; Syarifuddin Dollah; Sakkir, Geminastiti (Media Inovasi Pendidikan dan Pembelajaran, 2024)
This study aims to determine whether the snowball throwing technique in teaching the reading skills of class VIIIA students at MTs Negeri 1 Sidrap. This study employs quantitative research methods with a quasi-experimental design. The population under investigation consists of 25 students in class VIII A designated as the experimental group, and another 25 students in class VIII B designated as the control group at MTs Negeri 1 Sidrap, the samples were selected using the cluster random sampling technique. Data collection included pre-tests and post-tests. The data analysis results indicated a significant influence between the two tests. Therefore, it can be inferred that the utilization of snowball-throwing techniques has an impact on reading skills. So, in this research it was found that reading texts using the snowball throwing technique was used to improve reading skills of class VIIIA at MTs Negeri 1 Sidrap and the null hypothesis (H0) was accepted, indicating that the snowball throwing technique effectively enhanced the reading skills of class VIIIA students at MTs Negeri 1 Sidrap.